Moniuszko and Nowowiejski: analogies, contexts and inspirations - Dulisz, Ilona (Interdisciplinary Studies in Musicology, 2023)
The music of Stanisław Moniuszko and Feliks Nowowiejski constitutes a crucial element in Polish musical culture. The two composers forged their image on work focussed on national ideas, particularly in their stage works and songs. An important factor shaping their attitudes was the multi-cultural society in which they were raised and their awareness of national identity. Also presented in this article are Nowowiejski’s attitude to Moniuszko’s music and his presence in the latter’s works.